The role of peer support and mutual aid in reducing harm from alcohol, drugs and tobacco in 2020. (October 2020) - Manning, Victoria; Kelly, Peter J.; Baker, Amanda L.
Highlights: This Special Issue presents recent developments in and insights into peer support and mutual aid. Peer support should be offered as integrated/continuing care in addiction treatment. Alternatives to 12-Step approaches look promising but require empirical evaluation. Delivery modes (e.g., telephone, online) and peer roles have expanded.